2023
DOI: 10.1055/a-2174-0534
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning-based choledocholithiasis prediction tool to improve ERCP decision making: a proof-of-concept study

Steven N. Steinway,
Bohao Tang,
Brian S. Caffo
et al.

Abstract: Background: Prior studies have demonstrated that existing guidelines to predict choledocholithiasis have limited accuracy, leading to overutilization of ERCP. Improved stratification may allow for appropriate patient selection for ERCP and the use of lower-risk modalities (i.e. EUS and MRCP). Methods: A machine learning model was developed using patient information from two published cohort studies originally used to evaluate performance of published guidelines in predicting choledocholithiasis. Prediction mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…While the cutoff points suggested by ASGE were applied based on consensus, our study, along with prior research, indicates that the risk assignment for specific clinical and laboratory parameters-such as pancreatitis, bilirubin levels, and the diameter of the CBD-may exhibit variations. Steinway et al, 21 Zhang et al, 22 and Dalai et al 11 developed machine learning prediction models; nevertheless, we contend that our model possesses the ease of use and applicability to employ common variables outlined by the ASGE, making it adaptable in any setting.…”
Section: Discussionmentioning
confidence: 91%
“…While the cutoff points suggested by ASGE were applied based on consensus, our study, along with prior research, indicates that the risk assignment for specific clinical and laboratory parameters-such as pancreatitis, bilirubin levels, and the diameter of the CBD-may exhibit variations. Steinway et al, 21 Zhang et al, 22 and Dalai et al 11 developed machine learning prediction models; nevertheless, we contend that our model possesses the ease of use and applicability to employ common variables outlined by the ASGE, making it adaptable in any setting.…”
Section: Discussionmentioning
confidence: 91%
“…In this issue of Endoscopy, Steinway et al [1] present data using a gradient boosting machine learning model to predict the presence of CBD stones in patients with suspected choledocholithiasis. The goal of this research was to improve upon current stratification methods in patients with suspected choledocholithiasis to mitigate the risks associated with unnecessary ERCP procedures.…”
mentioning
confidence: 99%
“…
We are writing to express our great interest in the recent study by Steinway et al [1], which presents an impressive machine learning-based choledocholithiasis prediction model. The study demonstrated the feasibility of machine learning in gastroenterology, showing its strong clinical utility.
…”
mentioning
confidence: 99%